Pengaruh PAD dan Dana Perimbangan terhadap Kinerja Keuangan Pemerintah Kabupaten/Kota di Sumatera Selatan - Verawaty Verawaty; Ade Kemala Jaya; Intan Puspanita; Nurhidayah Nurhidayah (MBIA, 2020)
Abstract The financial performance of a regional government is the ability of a region to explore the financial potential of the region as well as to manage the local financial resources in order to meet the needs of the regional government so that it does not depend on the funding from the central government. This study was aimed to analyze whether fiscal balance transfers such as local own-source revenue, general allocation funds, special allocation funds, and revenue sharing funds might affect the government's financial performance. The study used quantitative analysis techniques with multivariate regression. The object of this research was the district and city governments in South Sumatra in 2014-2016. The results showed that local own-source revenue had a positive effect on the financial performance of local governments. However, there were negative effects of general and special allocation funds on regional government financial performance. For revenue sharing funds, it did not affect financial performance. This means, the greater the contribution of local own-source revenue to finance development and community services the greater increase in the financial performance of local governments. The higher the amount of general allocation funds received from the center, the lower the financial performance of local governments. The large flow of special allocation funds can provide opportunities for budget leakage, which can result in a decrease in the financial performance of local governments. Keywords: local own-source revenue, fiscal balance transfers, local government financial performance